Ethical Considerations in the Development and Application of Artificial Intelligence for Social and Economic Progress - Loso Judijanto; Jackson Yumame; Tanwir Tanwir; Gusma Afriani; Arnes Yuli Vandika (Edujavare Publishing, 2022)
This study investigates the ethical considerations surrounding the development and application of artificial intelligence (AI) for social and economic progress. This research aims to analyze the impact of AI on fairness, transparency, accountability, privacy, and social outcomes. The research method uses a systematic literature review (SLR) to collect and synthesize relevant findings from previous research and theoretical frameworks. The data is collected, and the data analysis technique used in the SLR method is to carry out stages such as study selection, evaluation of study quality, extraction of relevant data, and synthesis of findings from the selected studies. This research results in the importance of mitigating bias, increasing transparency and accountability, protecting privacy and data, and evaluating the social impact of AI. In conclusion, this research underscores the critical need for ethical frameworks and regulations to guide AI's responsible development and deployment to drive equitable and beneficial social and economic progress.